Participants in mathematics teacher education - Lloyd, Gwendolyn M.; Chapman, Olive (International handbook of mathematics teacher education, 2020)
Participants in Mathematics Teacher Education, focuses not only on prospective and practicing teachers as learners but also on school colleagues, teacher educators, researchers, and others who work to provide effective learning opportunities for teachers. The emphasis is on describing and analysing participants' engagement in mathematics teacher education collaborations and contexts from various perspectives. Thus, as the third volume in the series, it further broadens our understanding of the development of mathematics teachers.